2020
DOI: 10.3389/fphar.2020.00300
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Role of Salsalate in Diabetes Is Associated With Reducing Intestinal Inflammation Through Improvement of Gut Dysbiosis in ZDF Rats

Abstract: A safe and effective approach is needed to prevent and reduce the incidence of diabetes worldwide. The hypoglycemic efficacy of salicylic acid (salsalate, SAL), which has antiinflammatory properties, has been empirically demonstrated in studies conducted at the Joslin Diabetes Center and elsewhere. Here, we investigated the potential role of SAL in preventing the onset of diabetes in Zucker diabetic fatty (ZDF) rats and attempted to elucidate its underlying mechanisms. ZDF and Zucker lean (ZL) rats were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In addition, we found that the abundance of salicylic acid, which is derived from the catabolism of gut microbiota, decreased during LDA events. Zhang et al ( 44 ) reported that salicylic acid negatively modulates the abundance of Prevotella , further suppressing the inflammation response. Of note, 4-pyridoxic acid, cytidine, and salicylic acid were regarded as prediction factors of LDA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that the abundance of salicylic acid, which is derived from the catabolism of gut microbiota, decreased during LDA events. Zhang et al ( 44 ) reported that salicylic acid negatively modulates the abundance of Prevotella , further suppressing the inflammation response. Of note, 4-pyridoxic acid, cytidine, and salicylic acid were regarded as prediction factors of LDA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis, described as a disorder of or alteration in the density and/or composition of intestinal microbiota, may promote gut permeability, actuate innate immunity, regulate the metabolism of lipid and glucose, provoke light inflammatory responses, and lead to symptoms related to diabetes mellitus (Buford, 2017; Zhang et al., 2020). The intestinal barrier strictly maintains gut permeability via TJ complexes and a mucus layer, which prevents abnormal leakage and invasion of pathogen‐associated molecular patterns (PAMPs) into the circulation and separates gut microbiota and host molecules (Kim & Kim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al suggested that the mechanism by which salsalate improves glucose homeostasis and NAFLD is via salicylate-driven mitochondrial uncoupling ( Smith, et al, 2016 ). Antidiabetic effect of salsalate may be also related to reducing intestinal inflammation and improved gut dysbiosis that was observed in ZDF rats ( Zhang, et al, 2020 ). Although several studies have found increased adiponectin levels after salsalate administration ( Wang, et al, 2014 ; Salastekar, et al, 2017 ), which could contribute to improvement of insulin sensitivity, in the present study salsalate did not affect adiponectin levels.…”
Section: Discussionmentioning
confidence: 98%